Analisis Pengaruh Non Performing Loan (NPL), Return On Assets (ROA) dan Inflasi terhadap Tingkat Volume Kredit di LPD Desa Adat Kesiman - FEBRIYANTI, NI KADEK AYU MELLY; USTRIYANA, I NYOMAN GEDE; DEWI, NI LUH PRIMA KEMALA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Analysis Effect of Non Performing Loan (NPL), Return On Assets (ROA) and Inflation on The Level of Credit Volume in LPD Desa Adat Kesiman. Local credit institutions (Lembaga Perkreditan Desa, so called LPD) is a financial institution owned Pakraman village in the province of Bali. LPD has the task of fund collecting from community and fund distribution to the community in the form credit. The Covid-19 pandemic has an impact on LPD that is reducing credit payment and finishing credit payment. This study aims to analyze the effect of Non Performing Loan (NPL), Return On Assets (ROA), partial inflation and simultaneously to the level credit volume. In addition, this study aims to analyze the problem in resolving bad loans. The analysis method used was multiple linear regression and descriptive analysis. The results of this study indicate that NPL has a positive and significant influence on lending. ROA has a positive and insignificant effect on lending. Inflation has a negative and significant effect on lending. Simultaneously NPL, ROA, and inflation have a significant influence on credit distribution faced by LPD Desa Adat Kesiman there are 3, namely, collective (collateral), debtor's ability to pay credit, and loan balance that is not by customer needs.